Integration of Technology and Regulations for Safe and Efficient Marine Logistics - Habibi Palippui (Collaborate Engineering Daily Book Series, 2024)
Maritime logistics is at the heart of global trade, with nearly 90% of the world's cargo transported by sea. However, the industry faces significant challenges in ensuring safety, operational efficiency, and environmental sustainability amidst increasing trade volumes and demands to reduce carbon emissions. Integration of modern technology with existing regulatory frameworks is key to improving maritime logistics performance while complying with safety and environmental standards. This paper explores various current technologies that can be applied, such as real-time ship tracking systems with the Internet of Things (IoT) and wireless communications, automation of loading and unloading processes using robotics and artificial intelligence (AI), as well as the use of big data and predictive analytics for optimization route and fleet management. These technologies have the potential to increase supply chain visibility, and time efficiency, reduce human error, and optimize resources. On the other hand, international regulatory frameworks such as the Convention on the Safety of Life at Sea (SOLAS) and the Convention for the Prevention of Pollution from Ships (MARPOL) from the International Maritime Organization (IMO), as well as national and regional regulations related to shipping safety, the marine environment, maritime security, and labor, must be adhered to in adopting new technology.